القيم التنظيمية - شطي, أمينة; فريجة, أحمد (جامعة الوادي - University of Eloued, 2022)
الملخــص: تعتبر القيم التنظيمية من أهم المواضيع التي اهتمت بها العلوم الاجتماعية والإنسانية إذ أن أهميتها تكمن في كونها محرك إيجابي لسلوك أفراد العاملين في المؤسسة ، فالإدراك والاستخدام الأمثل للقيم السائدة داخل التنظيم والتي تجمع بين ما يحمله الرؤساء والمرؤوسين يعتبر الخيار الأفضل الذي يحقق أهداف المؤسسة ، لهذا ففهم ومعرفة القيم التنظيمية أمر مهم من أجل إدارة العاملين بنجاح ، وبالتالي فإن هدف الدراسة الحالية هو الإحاطة النظرية بموضوع القيم التنظيمية من خلال التطرق الى مختلـف المفـاهيم وإبراز أهم المراحل في تطور القيم التنظيمية وتصنيفاتها. Abstract: Organizational values are considered one of the most important topics to the interest of the social and human sciences, and their importance lies on being a positive driver for the behaviour of the employee in the organization . The realization and optimal use of the prevailing value within the organization, which combines what the superiors and subordinates carry, Is considered the best option aciehves the goals of the institution. Therefore, Knowing organizational values is important in order to manage employees succesfully, and therefore the aim of the current study is to brief the theoretical subject of organizational values by addressing various concepts of highlighting the most important stages in the development of organizational values and their classifications .
مقاربة نظرية
مقال
Keywords: القيم ، القيم التنظيمية ، الاتجاهات ، الأهداف ، السلوك